Receptor-based targeting of engineered nanocarrier against solid tumors: Recent progress and challenges ahead - Akhter, Md. Habban; Beg, Sarwar; Tarique, Mohammed; Malik, Arshi; Afaq, Sarah; Choudhry, Hani; Hosawi, Salman (Biochimica et biophysica acta. General subjects, 2021)
Background In past few decades, the research on engineered nanocarriers (NCs) has gained significant attention in cancer therapy due to selective delivery of drug molecules on the diseased cells thereby preventing unwanted uptake into healthy cells to cause toxicity. Scope of review The applicability of enhanced permeability and retention (EPR) effect for the delivery of nanomedicines in cancer therapy has gained limited success due to poor accessibility of the drugs to the target cells where non-specific payload delivery to the off target region lack substantial reward over the conventional therapeutic systems. Major conclusions In spite of the fact, nanomedicines fabricated from the biocompatible nanocarriers have reduced targeting potential for meaningful clinical benefits. However, over expression of receptors on the tumor cells provides opportunity to design functional nanomedicine to bind substantially and deliver therapeutics to the cells or tissues of interest by alleviating the bio-toxicity and unwanted effects. This critique will give insight into the over expressed receptor in various tumor and targeting potential of functional nanomedicine as new therapeutic avenues for effective treatment. General significance This review shortly shed light on EPR-based drug targeting using nanomedicinal strategies, their limitation, and advances in therapeutic targeting to the tumor cells. •Engineering nanocarriers have gained attention in cancer due to receptor targeting.•EPR based nanomedicines exhibit limited success due to poor drug retention in target cells.•TME is an important key domain for designing any NCs for effective drug targeting.•The active targeting is meant for improving targeting of NCs for better therapeutic efficacy.